2015
DOI: 10.1186/s12902-015-0073-7
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant growth hormone therapy in children with short stature in Kuwait: a cross-sectional study of use and treatment outcomes

Abstract: BackgroundRecombinant Growth hormone (rGH) therapy is approved in many countries for treatment of short stature in a number of childhood diagnoses. Despite the increasing body of international literature on rGH use, there is paucity of data on rGH use in Kuwait and the broader Middle-East which share unique ethnic and socio-cultural backgrounds. This study aimed to describe the pattern of use and treatment outcomes of rGH therapy in Kuwait.MethodsThis is a cross-sectional retrospective review of children treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 34 publications
0
5
1
Order By: Relevance
“…Many studies have shown that the use of rhGH can improve height gain and growth velocity in patients with ISS treated for a short period of time. However, the use of this medication in ISS might result in a rapid increase in bone age and early closure of the epiphyseal plate, which could eventually affect these patients' ability to attain expected adult height [9][10][11][12][13]. In contrast, many published research papers documented the efficacy of using rhGH in increasing the expected final adult height and growth velocity in patients with ISS [14][15][16][17][18][19][20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that the use of rhGH can improve height gain and growth velocity in patients with ISS treated for a short period of time. However, the use of this medication in ISS might result in a rapid increase in bone age and early closure of the epiphyseal plate, which could eventually affect these patients' ability to attain expected adult height [9][10][11][12][13]. In contrast, many published research papers documented the efficacy of using rhGH in increasing the expected final adult height and growth velocity in patients with ISS [14][15][16][17][18][19][20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence supporting the safety profile of GH therapy includes large registries comprising more than 600,000 patients-years of GH exposure, and long-term safety cohorts of adults who received GH therapy as children (22). Several studies have reported favorable outcomes of GH treatment in the Arabian Gulf region (23)(24)(25)(26). Despite this, only 60% of the respondents considered GH safe.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, approval has not been given by the EMA despite numerous applications by pharmaceutical companies [21]. Although a consensus approach to the diagnosis or treatment of ISS in GCC countries has not been established [6], it appears that FDA rather than EMA guidelines are generally followed, with approximately 20% of hGH-treated children having ISS as reported from Kuwait [51] and the UAE [52].…”
Section: Clinical Practice In Patients With Gh Deficiency (Ghd) Receimentioning
confidence: 99%